Premature ovarian insufficiency: a review on the role of tobacco smoke, its clinical harm, and treatment - Jinghan Cui; Ying Wang (BMC, 2024)
Abstract Premature ovarian insufficiency (POI) is a condition in which the quantity of follicles and the quality of oocytes gradually decrease. This results in an estrogen secretion disorder and abnormal follicle development, which can lead to related diseases, early onset of menopause, sexual dysfunction, and an increased risk of cardiovascular issues, osteoporosis, and depression, among others. This disease significantly impacts the physical and mental health and overall quality of life of affected women. Factors such as genetic abnormalities, oophorectomy, radiotherapy for malignancy, idiopathic conditions, and an unhealthy lifestyle, including smoking, can accelerate the depletion of the follicular pool and the onset of menopause. Extensive research has been conducted on the detrimental effects of tobacco smoke on the ovaries. This article aims to review the advancements in understanding the impact of tobacco smoke on POI, both in vivo and in vitro. Furthermore, we explore the potential adverse effects of common toxicants found in tobacco smoke, such as polycyclic aromatic hydrocarbons (PAHs), heavy metals like cadmium, alkaloids like nicotine and its major metabolite cotinine, benzo[a]pyrene, and aromatic amines. In addition to discussing the toxicants, this article also reviews the complications associated with POI and the current state of research and application of treatment methods. These findings will contribute to the development of more precise treatments for POI, offering theoretical support for enhancing the long-term quality of life for women affected by this condition.